FAKTOR KEBERHASILAN WIRAUSAHA DESA PADA PRODUK KEARIFAN LOKAL - Elistia Elistia; Lia Amalia; Rojuaniah Rojuaniah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Entrepreneurial success in Small and Medium Industries on local wisdom products is an important asset owned by a region. Sambas songket weaving is a product of local wisdom in West Kalimantan Province since the 16th century. This study aims to analyze the business success factors of the Sambas songket weaving entrepreneurs, totalling 30 respondents in Sumber Harapan Village, Sambas Regency. This research approach is an associative quantitative method with data processing by using hypothesis testing through the Structural Equation Model – Partial Least Square (SEM-PLS). The results of the research hypothesis test show that Social Capital (SC) and Innovation Capability (IC) have a positive and significant effect on Business Performance (BP), while Entrepreneurial Orientation (EO) has no positive and significant effect. The average value of respondents' answers sequentially is that the SC is the first, the second is BP, the third is IC, while the last is EO. So, it can be concluded that SC is the strength of sambas songket weaving entrepreneurs, IC is good enough to encourage business capacity, but EO must be a concern that must be increased in efforts to sustain entrepreneurship in local wisdom products.